Personality traits and skill competencies on community empowerment among Iban women in Sarawak - Yaccob, Yasmin; Adam Assim, Mohd Ibrani Shahrimin; Mat Jusoh, Nurul Hidayu; Jawan, Jayum; Zulkifli, Nurul Nadwa (Human Resource Management Academic Research Society, 2021)
This study proposed to investigate the power of personality and skills competencies of Iban population as the largest ethnic group in Sarawak. The influence of content and process on initiatives to empower the Iban women community in Sarawak will be an indicator of the measurement and evaluation of the program to the empowerment of Dayak women. This concept paper aims to critically review and identify gaps in the current literature on community empowerment, personality traits and skill competencies and come out with expected outcomes and recommendations for future research. This study applies a quantitative approach with a descriptive design through the questionnaire form for purpose of data collection. This study investigates five dimensions of the Big Five personality namely openness to experience, extroversion, agreeableness, conscientiousness, and neuroticism. This study also investigates three dimensions of skills competencies namely knowledge, skills, and attitudes. The findings of personality traits and skills competencies will be transformed into profiling data of Iban Women and proposed new initiatives and programs to empower Iban women. Overall, the findings will highlight and explain further the personality traits of Iban women, and the skills possessed for the market-appropriate job. Future studies are recommended to include more indicators like entrepreneur for enhancing Iban women empowerment initiatives in Sarawak.